Molecularly imprinted polypyrrole on glassy carbon electrode modified with reduced graphene oxide and gold nanoparticles for isoamyl alcohol analysis in fusel oil - Mariano, Thiago M. [UNESP]; Beluomini, Maísa A. [UNESP]; Stradiotto, Nelson R. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2021)
A molecularly imprinted electrochemical sensor for determination of isoamyl alcohol was successfully constructed by modifying the glassy carbon electrode (GCE) with gold nanoparticles (AuNPs) and reduced graphene oxide (RGO). The modification of the GCE increased the electron transfer rate and the electrode surface area, which, consequently, made more room available for the formation of the molecularly imprinted polymer (MIP). The development of the MIP on the modified surface was carried out via electropolymerization of the pyrrole in acetate buffer solution in the presence of the target molecule. The MIP-AuNPs-RGO/GCE showed low limit of detection (8.4 × 10-8 mol L-1), satisfactory quantification range, amperometric sensitivity of 1.1 A L mol-1, excellent reproducibility and stability. Even when in the presence of analogous molecules, the sensor exhibited excellent selectivity. These results suggest that the proposed sensor is suitable for the detection of isoamyl alcohol in fusel oil samples.
Keywords: Fusel oil; Gold nanoparticles; Isoamyl alcohol; Molecularly imprinted polypyrrole; Reduced graphene oxide